NEUROPROTECTIVE AND COGNITIVE ENHANCING EFFECT OF METHANOLIC MORUS ALBA LEAF FRACTION IN U87MG CELL LINES AND EXPERIMENTAL RAT MODEL - ANJALI RAJ,; SUMIT DEY,; SUBBA RAO VENKATA MADHUNAPANTULA,; MANJULA SN, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study aims to investigate the protective effect of methanol fraction of Morus alba (MEMA) leaves against hydrogen peroxide (H2O2)-induced U87MG cell toxicity and aluminum fluoride (ALF)-induced rat toxicity. Methods: The study was divided into in vitro and in vivo sections. U87MG cell lines were pre-treated with different fractions of MEMA for 20 h and further tested against 1000 ϻM of H2O2. The best fraction from in vitro studies was used to study the protective effects against ALF-induced neurotoxicity. Rats were divided i nto five different groups, and MEMA (200 and 400 mg/kg p.o) was administered for 14 days to the animals with α-tocopherol as the standard drug treatment. Behavioral studies were assessed using Barnes maze. The major biochemical measurements included catalase, superoxide dismutase and glutathione reductase, lipid peroxidation (LPO), and acetylcholinesterase (AchE) levels. Results: In vitro studies indicated MEMA as a potential candidate followed by AQMA and ethyl acetate. The MEMA fraction was able to ameliorate ALF-induced neurotoxicity in the behavioral assessment. The higher antioxidant content in the fraction decreased the LPO levels from 250±4.07 to 115±3.22 as well as elevated the levels of most of the endogenous antioxidant enzyme levels. AchE levels were also decreased to 33.89±0.71 from 38.94±0.64. Conclusion: Although the results obtained indicate that MEMA could significantly suppress oxidative stress-induced central neuronal damage both in vitro and in vivo, further mechanistic studies are required to delineate its neuroprotective pathway.